Aqueous compositions for elastomeric roof coatings
By using aqueous compositions of acrylic adhesives, zinc oxide and silane coupling agents in elastomeric roof coatings, the shortcomings of existing coatings in adhesion, acid resistance and low odor are solved, and efficient adhesion to polyester coated steel is achieved, while reducing ammonia release.
Patent Information
- Application Number
- CN202280096469.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-27
- Publication Date
- 2025-03-14
AI Technical Summary
The existing elastomeric roof coating compositions have shortcomings in adhesion, acid resistance and low odor, especially in poor adhesion to polyester coated steel.
An aqueous composition comprising an acrylic adhesive, zinc oxide and silane coupling agent is used, combined with a low ammonia acrylic adhesive latex, to enhance the adhesion, acid resistance and low odor characteristics of the coating through these ingredients.
Excellent adhesion to polyester coated steel was achieved, the initial tensile strength and elongation reached 2.0 MPa and above 200%, and the tensile strength of more than 80% and 100% elongation was maintained after acid treatment, while the ammonia release amount was less than 500 mg/kg.
Smart Images

Figure BDA0005152939720000091 
Figure BDA0005152939720000111 
Figure BDA0005152939720000112
Abstract
Description
Technical Field
[0001] The present disclosure relates to an aqueous composition for elastomeric roof coatings, particularly a low odor, acid resistant elastomeric roof coating composition having adhesion to polyester coated steel. Background Art
[0002] Elastomeric roof coating (ERC) compositions are typically used as liquid-applied, seamless, fully adhered flexible membranes formed on low-slope roofs. Elastomeric roof coatings provide benefits such as solar reflection for cooling buildings, reduced energy requirements for maintaining comfortable temperatures, etc. In addition, solar reflection can reduce the urban heat island effect. During use, water-based ERC formulations are preferred due to their low toxicity and reduced environmental impact when compared to solvent-based systems. In addition, all-acrylic latex adhesives have become the industry standard for ERC due to enhanced UV and mechanical durability relative to other commercial water-based adhesive technologies.
[0003] ERC compositions must balance the needs of mechanical strength (such as tensile strength) and the needs of elongation. In addition, ERC compositions should provide excellent durability, anti-fouling and adhesion to required substrates. In addition, according to JG / T 375-2012 and JC-1066-2008, ERC compositions require 500mg / kg or lower ammonia release, and must meet acid resistance requirements. Adhesion to low surface energy substrates such as coated steel substrates is a challenge, and key pigments / fillers are needed to achieve the balance between mechanical properties and application properties, particularly high tensile strength, high adhesion to colored steel plates and acid resistance. Currently available ERC compositions are unsatisfactory in one aspect or another.
[0004] Therefore, there is a need to provide a new waterborne composition for elastomeric roof coatings that can provide at least one of the following properties: low odor, ammonia release of 500 mg / kg or less, good acid resistance, and good adhesion to various substrates, particularly polyester coated steel. Summary of the invention
[0005] After continued exploration, the present inventors have surprisingly developed an aqueous composition for elastomeric roof coatings that exhibits excellent adhesion to various substrates, particularly polyester-coated steel, and preferably also exhibits low odor characteristics (e.g., low ammonia release) and / or good acid resistance.
[0006] In a first aspect of the present disclosure, there is provided an aqueous composition for an elastomeric roof coating, the aqueous composition comprising:
[0007] (1) an acrylic adhesive in an amount of 30.0 wt % to 50.0 wt % based on the total weight of the composition, the acrylic adhesive comprising
[0008] (i) 90% to 99.6% by weight, based on the weight of the acrylic adhesive, of an acrylic polymer, wherein the acrylic polymer comprises at least 90% by weight of acrylic or methacrylic repeating units; and
[0009] (ii) 0.4 wt % to 10.0 wt % of a (meth)acrylic acid monomer, based on the weight of the acrylic adhesive;
[0010] (2) zinc oxide in an amount of 1.5 wt % to 4.0 wt % based on the total weight of the composition;
[0011] (3) a silane coupling agent in an amount of 0.1 wt % to 0.5 wt % based on the total weight of the composition; and
[0012] (4) The remainder is water.
[0013] In a second aspect of the present disclosure, the present disclosure provides an elastomeric roof coating, comprising the aqueous composition according to claim 1 and ammonia added to the aqueous composition, wherein the amount of the ammonia is 0 wt % to 0.2 wt % based on the total weight of the elastomeric roof coating.
[0014] In a third aspect of the present disclosure, the present disclosure provides use of an acrylic adhesive in an elastomeric roof coating according to claim 6, wherein the acrylic adhesive comprises
[0015] (i) 90% to 99.6% by weight of an acrylic polymer, based on the weight of the acrylic adhesive, wherein the acrylic polymer comprises at least 90% by weight of acrylic or methacrylic repeating units;
[0016] (ii) 0.4 to 10.0 wt. % of a (meth)acrylic acid monomer; and
[0017] wherein the acrylic adhesive comprises less than 0.04 wt % ammonia based on the weight of the acrylic adhesive.
[0018] In a fourth aspect of the present disclosure, the present disclosure provides a method for preparing the elastomeric roof coating, the method comprising: (1) providing the aqueous composition for the elastomeric roof coating; and then (2) mixing ammonia with the aqueous composition, wherein the amount of ammonia is 0 wt % to 0.2 wt % based on the total weight of the elastomeric roof coating.
[0019] In the present disclosure, the elastomeric roof coating compositions can exhibit excellent adhesion to various substrates, particularly polyester coated steel. For example, the peel strength to colored steel is greater than 0.3 N / mm. For some elastomeric roof coating compositions, they can also exhibit low odor characteristics, for example, low ammonia release of less than 500 mg / kg of total ammonia present. In addition, the elastomeric roof coating compositions can exhibit good acid resistance, i.e., the initial tensile strength of the elastomeric roof coating is greater than 2.0 MPa; the initial elongation of the elastomeric roof coating is greater than 200%; and the tensile strength retention and elongation after acid treatment are greater than 80% and 100%, respectively.
[0020] It is to be understood that both the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention, as claimed. DETAILED DESCRIPTION
[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. As disclosed herein, "and / or" means "and, or as an alternative" or "in addition or alternatively". Unless otherwise indicated, all ranges are inclusive.
[0022] Unless otherwise indicated, all temperatures and pressures are at room temperature and standard pressure.
[0023] All phrases containing parentheses indicate either or both the inclusion of the parenthesized material and its absence. For example, in the alternative, the phrase "(meth)acrylate" includes acrylate and methacrylate.
[0024] Unless otherwise indicated, as used herein, the term "glass transition temperature" or "Tg" refers to the midpoint glass transition temperature of a polymer as determined by differential scanning calorimetry using a DSC Q2000 (TA Instruments, New Castle, Del.) according to ASTM E-1356 (1991), wherein a given emulsion copolymer is dried overnight at 60°C and subsequently cooled to a temperature of -70°C before scanning from -70°C to 130°C at a ramp rate of 20°C / min. The results are averaged over two runs (an initial run and a rescan run with a different sample of the same polymer).
[0025] As used herein, unless otherwise indicated, the term "coating thickness / thickness" refers to the average of at least three measurements of a dry coating (e.g., a dry film having a thickness of 0.8 mm to 1.2 mm) obtained by applying 3 wet films (e.g., having a thickness of about 1500 microns) on a release paper roofing substrate, as measured using an Ames Gage, Model 13C-B2600 (Ames Corporation Waltham Mass.).
[0026] As used herein, the term "(meth)acrylate" refers to acrylate, methacrylate, and mixtures thereof.
[0027] As used herein, the term "polymer" refers in the alternative to a polymer prepared from one or more different monomers, such as a copolymer, terpolymer, tetrapolymer, pentapolymer, etc., and may be any of a random polymer, a block polymer, a grafted polymer, a sequential polymer, or a gradient polymer.
[0028] As used herein, the term "pigment volume concentration" or %PVC refers to the amount calculated by the following equation:
[0029] %PVC = ((volume of pigment + volume of extender + volume of filler) / total dry volume of coating) × 100
[0030] As used herein, the term "total composition solids" or "solids" refers to any and every material in the composition other than water, ammonia, and volatile solvents, if any.
[0031] As used herein, unless otherwise indicated, the term "average particle size" means the weight average particle size determined by light scattering (LS) using a BI-90 particle size analyzer (Brookhaven Instruments Corp. Holtsville, NY).
[0032] As used herein, the term "weight average molecular weight" or "MW" refers to the weight average molecular weight measured by aqueous gel permeation chromatography (GPC) using polyacrylic acid (PAA) standards for aqueous solution polymers (e.g., polymeric polyacids) and polystyrene standards for aqueous emulsion copolymers.
[0033] As used herein, the phrase "wt %" means percent by weight.
[0034] According to the present invention, the aqueous composition for an elastomeric roof coating comprises an acrylic binder in an amount of 30.0 wt % to 50.0 wt %, 30.0 wt % to 45.0 wt %, 30.0 wt % to 40.0 wt %, 30.0 wt % to 35.0 wt %, 35.0 wt % to 50.0 wt %, 35.0 wt % to 45.0 wt %, 35.0 wt % to 40.0 wt %, 40.0 wt % to 50.0 wt %, 40.0 wt % to 45.0 wt % or 45.0 wt % to 50.0 wt %, based on the total weight of the composition. The acrylic adhesive may comprise (i) 90 wt % to 99.6 wt %, 92 wt % to 99.6 wt %, 94 wt % to 99.6 wt %, 96 wt % to 99.6 wt %, or 98 wt % to 99.6 wt % of an acrylic polymer, wherein the acrylic polymer comprises at least 90 wt %, at least 92 wt %, at least 94 wt %, at least 96 wt %, or at least 98 wt % acrylic or methacrylic repeating units; and (ii) 0.4 wt % to 10.0 wt %, 0.4 wt % to 8.0 wt %, 0.4 wt % to 6.0 wt %, 0.4 wt % to 4.0 wt %, or 0.4 wt % to 2.0 wt % of a (meth)acrylic monomer, based on the weight of the acrylic adhesive.
[0035] In one embodiment of the present disclosure, the acrylic adhesive may have a pH in the range of 4.0 to 7.0, 4.0 to 6.0, 4.0 to 5.0, 5.0 to 7.0, 5.0 to 6.0, or 6.0 to 7.0; and a glass transition temperature (Tg) of -40°C to -15°C; -40°C to -20°C; -40°C to -25°C; -40°C to -30°C; -40°C to -35°C; -35°C to -15°C; -35°C to -20°C; -35°C to -25°C; -35°C to -30°C; -30°C to -15°C; -30°C to -20°C; -30°C to -25°C; -25°C to -15°C; -25°C to -20°C, or -20°C to -15°C. In the present disclosure, the acrylic polymer has an average molecular weight of 50 kDa to 2000 kDa, 50 kDa to 1500 kDa, 50 kDa to 1000 kDa, 50 kDa to 500 kDa, 50 kDa to 200 kDa, 200 kDa to 2000 kDa, 200 kDa to 1500 kDa, 200 kDa to 1000 kDa, 200 kDa to 500 kDa, 500 kDa to 2000 kDa, 500 kDa to 1500 kDa, 500 kDa to 1000 kDa, 1000 kDa to 2000 kDa, 1000 kDa to 1500 kDa, or 1500 kDa to 2000 kDa. In addition, the use of acrylic polymers having such molecular weights can increase the %PVC of compositions containing them.
[0036] In one embodiment of the present disclosure, the (meth)acrylic monomer includes, but is not limited to, (meth)acrylic acid, alkyl (meth)acrylates, and 2-hydroxyethyl (meth)acrylate phosphate.
[0037] In one embodiment of the present disclosure, the acrylic adhesive has an ammonia content of less than 0.04 wt%. In one embodiment of the present disclosure, the acrylic adhesive is included in the aqueous composition as the only adhesive. In one embodiment of the present disclosure, the aqueous composition further comprises at least one inert filler, the amount of the at least one inert filler being 30 wt% to 35 wt% based on the total weight of the composition. In one embodiment of the present disclosure, the inert filler is selected from BaSO4, kaolin, silica powder, talc, aluminum trihydrate or a combination thereof.
[0038] The peel strength (adhesion) of commercially available ERC is a challenging property for ERC when applied to certain substrates such as concrete, metal, asphalt, etc. Different primers can be used to enhance adhesion to the selected substrate, but these primers are generally solvent-based and result in increased application complexity and increased material and labor costs. Adhesion to selected substrates such as polyesters used to coat steel is a particular challenge due to the inherent low surface energy of the substrate. A key application of ERC is the coating of polyester-coated steel (non-ferrous steel) metal roof systems. Surprisingly, the inventors of the present invention have found that the use of a ZnO crosslinker together with an acrylic adhesive and a silane coupling agent can enhance film strength and adhesion to non-ferrous steel, achieving balanced mechanical properties and application properties, especially high tensile strength, high adhesion to non-ferrous steel, and acid resistance.
[0039] According to the present invention, the aqueous composition for elastomeric roof coatings comprises zinc oxide in an amount of 1.5 wt % to 4.0 wt %, 1.5 wt % to 3.8 wt %, 1.5 wt % to 3.5 wt %, 1.5 wt % to 3.0 wt %, 1.5 wt % to 2.5 wt %, 1.5 wt % to 2.0 wt %, 2.0 wt % to 4.0 wt %, 2.0 wt % to 3.8 wt %, 2.0 wt % to 3.5 wt %, based on the total weight of the composition. %, 2.0 wt % to 3.0 wt %, 2.0 wt % to 2.5 wt %, 2.5 wt % to 4.0 wt %, 2.5 wt % to 3.8 wt %, 2.5 wt % to 3.5 wt %, 2.5 wt % to 3.0 wt %, 3.0 wt % to 4.0 wt %, 3.0 wt % to 3.8 wt %, 3.0 wt % to 3.5 wt %, 3.5 wt % to 4.0 wt %, 3.5 wt % to 3.8 wt %, or 3.8 wt % to 4.0 wt %. In one embodiment of the present disclosure, zinc oxide is used as an acid-reactive filler that attaches to the acid on adjacent polymer chains, creating a tightly woven polymer network in the coating, resulting in reduced water absorption, increased tensile strength, and improved water resistance.
[0040] According to the present invention, the aqueous composition for elastomeric roof coatings comprises a silane coupling agent in an amount of 0.1 wt % to 0.5 wt %, 0.1 wt % to 0.4 wt %, 0.1 wt % to 0.3 wt %, 0.1 wt % to 0.2 wt %, 0.2 wt % to 0.5 wt %, 0.2 wt % to 0.4 wt %, 0.2 wt % to 0.3 wt %, 0.3 wt % to 0.5 wt %, 0.3 wt % to 0.4 wt % or 0.4 wt % to 0.5 wt %. In one embodiment of the present disclosure, the silane coupling agent includes but is not limited to aminosilane, epoxysilane, vinylsilane, methacryloxysilane, etc. The silane coupling agent can combine the inorganic filler with the polymer to improve the strength and water resistance of the coating film. The zinc oxide, silane coupling agent and acrylic adhesive disclosed in the present disclosure will significantly improve the adhesion to low-energy surface substrates such as colored steel plates.
[0041] According to the present invention, the aqueous composition for an elastomeric roof coating may be substantially free of organic solvents. In particular, the remainder of the aqueous composition for an elastomeric roof coating is water, for example, deionized water.
[0042] According to the present invention, the aqueous composition for elastomeric roof coatings essentially comprises or consists of an acrylic binder, zinc oxide, a silane coupling agent and water. Alternatively, the acrylic binder is the only binder in the aqueous composition. According to the present invention, the aqueous composition for elastomeric roof coatings has an ammonia content of less than 0.04% by weight. Alternatively, the acrylic binder essentially comprises or consists of 90% to 99.6% by weight of an acrylic polymer based on the weight of the acrylic binder and 0.4% to 10.0% by weight of (meth)acrylic acid monomers based on the weight of the acrylic binder, wherein the acrylic polymer comprises at least 90% by weight of acrylic or methacrylic repeating units. In a preferred embodiment of the present invention, the aqueous composition comprises a low ammonia acrylic binder latex (ammonia content less than 0.035%, less than 0.033%, less than 0.028% or less than 0.02%) as the only binder. Also provided in the present disclosure is the use of an acrylic adhesive, particularly a low ammonia acrylic adhesive, as the sole latex binder in an elastomeric roof coating.
[0043] In the present invention, the acid resistance of ERC coating is mainly affected by the extender / filler. Generally speaking, calcium carbonate, silica powder, talcum powder, etc. are widely used in coating formulations, but they react with acid and cause strength failure. According to the present invention, the aqueous composition for elastomeric roof coatings may further comprise: (5) at least one inert filler, the amount of which is 30% to 35% by weight or 30% to 32% by weight based on the total weight of the composition. According to the present invention, conventional extenders or fillers (e.g., calcium carbonate) are replaced with inert fillers such as kaolin, BaSO4, etc., so as to improve the strength retention rate of the coating after acid treatment. In one embodiment, the inert filler is selected from BaSO4, kaolin, silica powder, talcum powder, aluminum hydroxide or a combination thereof.
[0044] In one embodiment of the present disclosure, the aqueous composition further comprises (5) at least one inert filler, the amount of which is 30 wt % to 35 wt % based on the total weight of the composition. In one embodiment of the present disclosure, the inert filler is selected from BaSO4, kaolin, silica powder, talc, aluminum hydroxide or a combination thereof.
[0045] In some embodiments of the present disclosure, the aqueous composition for elastomeric roof coatings of the present invention may include conventional fillers and processing aids for elastomeric roof coatings, as long as the amount of ammonia is limited to the desired level. The aqueous composition for elastomeric roof coatings is colored and also contains an extender or filler. Suitable pigments can be opacifiers, for example, pigments or polymer pigments containing titanium dioxide, hollow spheres or voids; iron oxide, IR reflective pigments or zinc oxide. Suitable extenders can be, for example, clay, mica, talc, aluminum silicate, aluminum trihydrate, nepheline syenite or any mixture of these with other extenders. Fillers and extenders are considered to be the same substance. If desired, the aqueous composition of the present invention may also include one or more extenders (such as nepheline syenite) and one or more pigments (such as titanium dioxide or iron oxide). Transparent ERC compositions can be formulated with extenders without pigments.
[0046] In one embodiment of the present disclosure, the aqueous composition for elastomeric roof coatings may have a solid content in the range of 65 wt % to 70 wt %, based on the total weight of the composition. The solid content of the aqueous component of the present invention may be in the range of 60 wt % to 75 wt % or 65 wt % to 70 wt %. Solids in the present invention include any fillers, extenders and pigments and any solid additives present in the coating or film made from the composition.
[0047] The aqueous composition for elastomeric roof coatings of the present invention may have a pigment volume concentration (%PVC) of 30 to 50, preferably 30 to 45, or more preferably 35 to 45. A total volume of pigments, extenders, and / or opacifiers exceeding 50%PVC may generally impair elongation, while a lack of sufficient volume of such materials may impair the tensile strength of a coating made from the aqueous composition of the present invention.
[0048] According to the present invention, an elastomeric roof coating composition is prepared by adding an ammonia-containing precursor (preferably aqueous ammonia) as a neutralizing agent to an aqueous composition, which preferably contains a low-ammonia acrylic adhesive. In the present disclosure, the acrylic adhesive has an ammonia content of less than 0.04% by weight; or it eliminates any step of post-adding ammonia in the acrylic adhesive, which can still maintain mechanical and thermal storage stability. At the same time, ammonia or aqueous ammonia can be subsequently added to the aqueous composition to neutralize and stabilize the ERC composition. The method reduces the total ammonia release of the formed elastomeric roof coating to less than 500 mg / kg, while shortening the drying time for the ERC composition, which is critical for early rain resistance. The inventors surprisingly found that, in contrast to the present invention, the use of commonly used acrylic adhesives containing post-added ammonia, together with the elimination of the addition of ammonia or aqueous ammonia to the aqueous composition, does not reduce the total ammonia release of the resulting elastomeric roof coating to less than 500 mg / kg, as required by JC-1066-2008 "Limit of harmful substances of building waterproof coatings". The elastomeric roof coating composition comprises or consists of an aqueous composition and ammonia in an amount of 0 wt % to 0.2 wt %, 0 wt % to 0.15 wt %, 0 wt % to 0.1 wt %, 0 wt % to 0.05 wt %, 0.05 wt % to 0.2 wt %, 0.05 wt % to 0.15 wt %, 0.05 wt % to 0.1 wt %, 0.1 wt % to 0.2 wt %, 0.1 wt % to 0.15 wt %, or 0.15 wt % to 0.2 wt %, based on the total weight of the elastomeric roof coating composition.
[0049] In one embodiment of the present disclosure, the elastomeric roof coating may have a pH in the range of 7.0 to 9.0, 7.0 to 8.0, or 8.0 to 9.0; and have a low ammonia release of less than 500 mg / kg, less than 400 mg / kg, less than 300 mg / kg, or less than 200 mg / kg of total ammonia present.
[0050] According to the present invention, the elastomeric roof coating composition can exhibit excellent adhesion to various substrates, especially polyester-coated steel. For example, the peel strength to the colored steel plate is higher than 0.3 N / mm. In addition, the elastomeric roof coating composition can exhibit good acid resistance, that is, the initial tensile strength of the elastomeric roof coating is higher than 2.0 MPa; the initial elongation of the elastomeric roof coating is higher than 200%; and the tensile strength retention and elongation after acid treatment are higher than 80% and 100%, respectively.
[0051] Example
[0052] Some embodiments of the present invention will now be described in the following examples, in which all parts and percentages are by weight unless otherwise specified.
[0053] The information of the raw materials used in the examples is listed in Table 1 below:
[0054] Table 1. Raw materials used in the examples
[0055]
[0056] Examples 1 to 3 of the present invention and Comparative Examples 1 to 2
[0057] In the inventive examples 1 to 3 of the present disclosure, low ammonia acrylic adhesive latex was synthesized based on the above commercial acrylic adhesive latex described in Table 1 and process development was performed, which reduced the ammonia content in the acrylic adhesive latex and maintained stability. In comparative examples 1 and 2, they used DOW commercial products and 2-component blended latex, respectively.
[0058] Table 2. Formulations used in the examples
[0059] raw materials Weight / kg Grinding A Deionized water 144.5 Nopco NXZ 3 <![CDATA[Orotan TM 1850E]]> 4 B Titanium Dioxide 72 Inert filler 330 ZnO 20 Thinning C Acrylic adhesive latex 403 Nopco NXZ 3 D Texanol 6 E Ammonia (28%) 0.6 F <![CDATA[Natrosal TM 250HBR]]> 3.5 G OFS-6040 1.5 total 991.1 solid% 65.70 PVC% 39.37
[0060] The formulations in Examples 1 to 3 of the present invention were prepared according to the following method:
[0061] (1) During the grinding process, the initial ingredients A of the grind are charged into a mixing kettle.
[0062] (2) While mixing at low speed, add Pigment B to the kettle.
[0063] (3) Add half of Premix F (with DI water) to kettle.
[0064] (4) After all the pigment is added to the kettle, stop the mixer and scrape the sides and bottom of the kettle.
[0065] (5) Turn the mixer back on and grind the contents of the mixer at high speed for 15 to 30 minutes, or until a good grind is obtained (Hegman reading of 4.5 to 5.0).
[0066] (6) For the letdown process, add the C latex emulsion to the kettle. Add a "layer" of defoamer on top of the Primal EC emulsion.
[0067] (7) Open the mixer and blend the contents of the mixer together.
[0068] (8) While blending, add ingredients D and E to the kettle.
[0069] (9) Immediately after adding the NH4OH to the mixture, add the remaining half as a premix of ingredient F. Add ingredient F within 5 minutes of the NH4OH or the necessary thickening time will increase significantly.
[0070] (10) Component (G) is added later.
[0071] Table 3: Acrylic Adhesive Latex Properties :
[0072]
[0073] Table 3 shows that the acrylic adhesive latex has good mechanical and thermal storage stability with less ammonia in the overall formulation at pH 5 to 6.
[0074] Table 4: Formulation
[0075]
[0076]
[0077] In Table 4, Inventive Example 1 / Example 2 comprise low ammonia latex, ZnO filler (instead of CaCO3 (DOW ARM-91-1) in Comparative Example 1) and silane; whereas Comparative Example 2 uses a 2-component adhesive latex and different fillers / pigments.
[0078] Testing and Evaluation
[0079] Experimental adhesives were synthesized in the Sanshui plant according to the recipes listed above, producing several commercial latexes, removing post-added ammonia as well as the biocide package in the final processing steps. Basic properties of the latexes, such as pH, viscosity, solids content %, thermal storage stability, mechanical stability were confirmed by standard test protocols.
[0080] Sample preparation and testing are carried out in accordance with JG / T 375-2012 "Acrylic Waterproof Coating for Metal Roof". 1. JG / T 375-2012 "Acrylic Waterproof Coating for Metal Roof" is summarized as follows:
[0081] (1) Initial tensile strength ≥1.5MPa (≥*2.0MPa);
[0082] (2) Initial elongation % ≥ 150 (* ≥ 200);
[0083] (3) Water absorption ≤ 15%;
[0084] (4) Low temperature flexibility at -30℃
[0085] (5) The tensile strength retention rate after acid treatment is ≥80%;
[0086] (6) The tensile elongation after acid treatment is ≥ 100%;
[0087] (7) Peel strength for non-ferrous steel ≥ 0.3N / mm, etc. (* ≥ 0.5)
[0088] * Obtained in the present invention.
[0089] Sample preparation
[0090] Before coating, the samples prepared according to the formulation in Table 2 were conditioned at (23 ± 2) ° C and (50 ± 10)% relative humidity for more than 24 hours. They were stirred and poured into the specified mold for coating without mixing bubbles. The coating film was prepared by applying 3 coats. Before applying the subsequent coat, each coat was dried for up to 24 hours to form an integrated film suitable for release and not torn when removed. The coating thickness of the total film was controlled to (1.0 ± 0.2) mm within 48 hours of drying. The film was fully cured at 23 ° C and 50% relative humidity for 96 hours, then removed from the release paper and placed in a (40 ± 2) ° C oven for 48 hours to fully cure. Before testing, the film should be conditioned at (23 ± 2) ° C and (50 ± 10)% relative humidity for more than 4 hours.
[0091] Solid content
[0092] The ERC solid content was tested according to JG / T 375-2012 using 0.6 g sample, dried in an oven at (105±2)°C for 3 times and repeated for (180±15) minutes.
[0093] Initial tensile strength and elongation
[0094] The tensile strength was measured according to GB / T 16777-2008 test method 9.2.1. The tensile speed was 200 mm / min. The Chinese standard specification JG / T 375-2012 requires that the coating have an initial tensile strength of ≥1.5 MPa and an initial elongation of ≥150% at 23°C.
[0095] Acid treatment and subsequent tensile strength and elongation
[0096] Six rectangular specimens (120*25) mm were placed in a 2% H2SO4 solution. The liquid level was kept 10 mm higher than the surface of the test piece. After continuous immersion for 168±1 hours, the test pieces were taken out, washed thoroughly with water, and dried in an oven for 6 hours±15 minutes. They were then placed under standard test conditions of 23±2°C and 50±10% relative humidity for 18±2 hours, and cut into I-shaped shapes according to the requirements of GB / T528-2009, and tested according to the test method specified in 9.2.4 of GB / T 16777-2008.
[0097] Peel strength on non-ferrous steel
[0098] According to GB / T 12754, three rectangular specimens of 200mm X 200mm polyester-coated colored steel were taken as substrates. The tensile strength MD of the non-woven PET fabric was ≥150N / 50mm, the rectangle was 420mm X 200mm, and the thickness was 0.3mm to 0.5mm. The coating film was prepared by applying 3 coats. Before applying the subsequent coat, each coat was dried for up to 24 hours to form an integrated film suitable for release and not torn when removed. The non-woven PET fabric was coated with the second coat. The thickness of the total film was controlled to (1.5±0.2) mm within 48 hours of drying. The film was fully cured at 23°C and 50% relative humidity for 96 hours, then removed from the release paper and placed in a (40±2)°C oven for 48 hours to fully cure. Before testing, the film should be conditioned at (23±2)°C and (50±10)% relative humidity for more than 4 hours. The sample was cut into 5 specimens and immersed in water for 168 hours. According to Appendix A of JG / T375-2012, the peeling speed is 50 mm / min, the minimum peeling length is 115 mm, and the peeling strength requirement is ≥ 0.3 N / mm.
[0099] Ammonia Release
[0100] Ammonia is distilled from the alkaline solution and absorbed with excess sulfuric acid standard solution. Using a mixed indicator of methyl red and methylene blue, according to the 4.1A level requirement of JC-1066-2008 "Limits of Hazardous Substances in Building Waterproof Coatings", ammonia ≤ 500mg / kg, excess sulfuric acid is titrated with sodium hydroxide standard titration solution. (JC-1066-2008 "Limits of Hazardous Substances in Building Waterproof Coatings": Level A, VOC ≤ 80g / L; Formaldehyde ≤ 100g / L; Benzene series ≤ 300g / L; Ammonia ≤ 500mg / kg).
[0101] Coating drying time (GB1728-1979 "Testing method for drying time of coating and topcoat (Testing method for drying time of coating and topcoat ( Methods for the Drying Time of Coating FilmsandSkim Coat)》) :
[0102] The coating liquid was applied on the top of the standard experimental fiber cement panel by a 1000um thick applicator. The surface drying time (dry to touch) and complete drying time were tested in an area at least 1 cm away from the edge of the coating using the following test method.
[0103] Surface drying time (dry to touch)
[0104] Carefully touch the surface of the coating with your finger. If the coating feels tacky but no coating is left on your finger, it is considered dry to touch. Record the time as the surface dry time.
[0105] Complete drying time
[0106] Use a knife to cut through the coating to carefully observe the bottom and inner cross-section of the coating. If there is no stickiness, it is considered completely dry. Record the time as the complete drying time.
[0107] Table 5: ERC properties :
[0108]
[0109] Table 5 shows the coating properties, which demonstrate that the ammonia release of the ERC formulation of the present invention was significantly reduced from approximately 1000 mg / kg to 160 mg / kg.
[0110] Table 6: Results for stretching and acid-treated stretching :
[0111]
[0112] Table 6 shows the mechanical properties of strength / elongation before and after acid treatment. ZnO filler (Examples 1 / 2 of the present invention and Comparative Example 1) can significantly improve the initial strength / elongation by about 50% to 60%, and the filler of the present invention can also greatly improve the elongation after acid treatment. The experimental results show that the low-ammonia acrylic adhesive latex incorporated into the ERC matrix together with the inert filler has better coverage, interaction and higher cross-linking density, which contributes to the mechanical strength and acid resistance of ERC. In addition, the tensile strength retention of Example 3 of the present invention using silica powder and BaSO4 dropped to 54%.
[0113] Table 7: Summary results for heat aging and adhesion
[0114]
[0115] Table 5 shows that the adhesion (peel strength) of the ERC formulation of the present invention is much higher than that of Comparative Example 2, which is attributed to the incorporation of the coupling agent silane and low ammonia acrylic binder latex into the coating formulation along with the ERC.
[0116] Based on all the above performance comparisons, it is confirmed that:
[0117] 1. The low ammonia acrylic binder latex of the present invention enables the ERC composition to reduce ammonia emission to less than 500 mg / kg, and its bonding with the ERC coating substrate contributes to mechanical strength.
[0118] 2. Compared with the prior art (eg, DOW ARM-91-1 in Comparative Example 1), the ERC composition of the present invention can maintain as much mechanical strength / elongation after acid treatment and can show excellent acid resistance.
[0119] 3. Compared with the prior art (e.g., Comparative Example 2), the ERC composition of the present invention uses a low-ammonia acrylic adhesive latex instead of a two-component blended acrylic latex, and it uses ZnO, an inert filler, and a silane coupling agent to balance the mechanical strength and acid resistance of the ERC, and further significantly enhances the adhesion to non-ferrous steel.
[0120] 4. Low ammonia latex ERC composition is a new composition with low odor, good acid resistance, higher adhesion to polyester coated steel, and meets the requirements of JC-1066-2008 "Limits of Hazardous Substances in Building Waterproof Coatings" Class A and JG / T 375-2012 "Metal Roof Acrylic High Elastic Waterproof Coating".
Claims
1. An aqueous composition for an elastomeric roof coating, the aqueous composition comprising: (1) an acrylic adhesive in an amount of 30.0 wt % to 50.0 wt % based on the total weight of the composition, wherein the acrylic adhesive comprises (i) 90% to 99.6% by weight, based on the weight of the acrylic adhesive, of an acrylic polymer, wherein the acrylic polymer comprises at least 90% by weight of acrylic or methacrylic repeating units; and (ii) 0.4 wt % to 10.0 wt % of a (meth)acrylic acid monomer, based on the weight of the acrylic adhesive; (2) zinc oxide in an amount of 1.5 wt % to 4.0 wt % based on the total weight of the composition; (3) a silane coupling agent in an amount of 0.1 wt % to 0.5 wt % based on the total weight of the composition; and (4) The remainder is water.
2. The aqueous composition for an elastomeric roof coating according to claim 1, wherein the acrylic adhesive comprises less than 0.04% ammonia by weight of the acrylic adhesive.
3. The aqueous composition for an elastomeric roof coating according to claim 1, wherein the acrylic binder is the only binder in the aqueous composition.
4. The aqueous composition for an elastomeric roof coating according to claim 1, wherein the aqueous composition further comprises: (5) at least one inert filler, in an amount of 30% by weight based on the total weight of the composition to 35 wt%.
5. The aqueous composition for an elastomeric roof coating according to claim 4, wherein the inert filler is selected from BaSO4, kaolin, silica powder, talc, aluminum hydroxide or a combination thereof.
6. An elastomeric roof coating comprising the aqueous composition according to claim 1 and ammonia post-added to the aqueous composition, wherein the amount of ammonia is 0 wt% to 0.2 wt% based on the total weight of the elastomeric roof coating.
7. The elastomeric roof coating of claim 6, wherein the acrylic adhesive comprises less than 0.04% ammonia by weight of the acrylic adhesive; and the total ammonia emission of the elastomeric roof coating is less than 500 mg / kg.
8. The elastomeric roof coating of claim 6 wherein the acrylic binder is the only binder in the aqueous composition.
9. The elastomeric roof coating of claim 6, wherein the aqueous composition further comprises: (5) at least one inert filler in an amount of 30 to 35 weight percent based on the total weight of the composition.
10. The elastomeric roof coating according to claim 6, wherein the inert filler is selected from BaSO4, kaolin, silica powder, talc, aluminum hydroxide or a combination thereof.
11. Use of an acrylic adhesive in the elastomeric roof coating according to claim 6, wherein the acrylic adhesive comprises (i) 90% to 99.6% by weight, based on the weight of the acrylic adhesive, of an acrylic polymer, wherein the acrylic polymer comprises at least 90% by weight of acrylic or methacrylic repeating units; (ii) 0.4 to 10.0 wt. % of a (meth)acrylic acid monomer; and wherein the acrylic adhesive comprises less than 0.04% ammonia by weight of the acrylic adhesive.
12. A method for preparing the elastomeric roof coating according to claim 6, the method comprising: (1) providing the aqueous composition according to claim 1; And then (2) mixing ammonia with the aqueous composition, wherein the amount of ammonia is 0 wt % to 0.2 wt % based on the total weight of the elastomeric roof coating.
13. The method of claim 12, wherein the acrylic adhesive comprises less than 0.04 wt% ammonia based on the weight of the acrylic adhesive; the acrylic adhesive is the only adhesive in the aqueous composition; and / or the aqueous composition further comprises at least one inert filler in an amount of 30 wt% to 35 wt% based on the total weight of the composition.
14. The elastomeric roof coating according to claim 12, wherein the inert filler is selected from BaSO4, kaolin, silica powder, talc, aluminum hydroxide or a combination thereof.